2016
DOI: 10.5334/pb.308
|View full text |Cite
|
Sign up to set email alerts
|

Measures of Implicit Gender Attitudes May Exaggerate Differences in Underlying Associations among Chinese Urban and Rural Women

Abstract: The oppression of women in rural China is more severe than in urban China, not only because the two areas differ in terms of social hierarchy, but also because urban women are more likely to fight against their subordination, which is endorsed by conventional social views on gender. To independently assess these relationships, we applied the Quadruple Process model to measure the processes underlying implicit gender attitudes in a sample of urban and rural females. The results indicated that the urban women ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…Consistent with the literature ( Jin et al, 2016 , Vuletich et al, 2023 ), the study found that the geographical location of practice significantly influenced Arab IAT scores, with pharmacists practicing in towns displaying higher scores than those in cities. Urban areas, such as cities, often have a greater level of racial and ethnic diversity compared to smaller towns.…”
Section: Discussionsupporting
confidence: 88%
“…Consistent with the literature ( Jin et al, 2016 , Vuletich et al, 2023 ), the study found that the geographical location of practice significantly influenced Arab IAT scores, with pharmacists practicing in towns displaying higher scores than those in cities. Urban areas, such as cities, often have a greater level of racial and ethnic diversity compared to smaller towns.…”
Section: Discussionsupporting
confidence: 88%
“…First, policies should be developed to promote gender equality in both self-employment and wage-employment. The finding that women experience lower levels of well-being than men in both types of employment indicates that policies, such as childcare support and maternity leave, efforts to reduce or eliminate gender discrimination, and promotion of equitybased gender attitudes in both wage-employment and selfemployment (e.g., networking, fund-raising, hiring, promotion, and compensation) are imperative (Cebi and Wang, 2013;Jin et al, 2016;Cooke, 2022). These policies will stimulate positive outcomes beyond the economy and help foster a level playing field for all.…”
Section: Discussionmentioning
confidence: 99%